Représenter la victoire militaire d’une femme - Marjolaine Massé (Les Cahiers de l'École du Louvre)
The standard of Queen Gerberge is a device to demonstrate power, the outcome of a specific historical context, and it reflects both the special relationship of queens with power and the art of embroidery. Embroidery was a key means of expression for the women of the elite class during the early Middle Ages, which allowed them to more easily leave their mark as forces of influence. The image here circumvents the impossibility of showing a woman as a warrior yet presents a demonstration of power through its materiality and its triumphant imperial iconography. It is also indicative of a time when sovereigns – in need of dynastic legitimacy for power they have usurped – attempted to consolidate their lineage, here with the use of imagery, on a volatile political chessboard.